Influence of Ultra-Violet Radiation on Sublimation Energy of Silver Chloride (AgCl); Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Mostovshchikov A. V. Andrey Vladimirovich (Chemical Engineering and Technology, 2016)
Title screen